Expert opinion paper on atrial fibrillation detection after ischemic stroke - Häusler, Karl Georg; Steiner, Thorsten (Clinical research in cardiology, 2018)
This expert opinion paper on atrial fibrillation detection after ischemic stroke includes a statement of the “Heart and Brain” consortium of the German Cardiac Society and the German Stroke Society. This paper was endorsed by the Stroke Unit-Commission of the German Stroke Society and the German Atrial Fibrillation NETwork. In patients with ischemic stroke, detection of atrial fibrillation should usually lead to a change in secondary stroke prevention, since oral anticoagulation is superior to antiplatelet drugs. The detection of previously undiagnosed atrial fibrillation can be improved in patients with ischemic stroke to optimize stroke prevention. This paper summarizes the present knowledge on atrial fibrillation detection after ischemic stroke. We propose an interdisciplinary standard for a “structured analysis of ECG monitoring” on the stroke unit as well as a staged diagnostic scheme for the detection of atrial fibrillation. Since the optimal duration and mode of ECG monitoring has not yet been finally established, this paper is intended to give advice to physicians who are involved in stroke care. In line with the nature of an expert opinion paper, labeling of classes of recommendations is not provided, since many statements are based on the expert opinion, reported case series and clinical experience. Therefore, this paper is not intended as a guideline.